RESPON MASYARAKAT TERHADAP PENGELOLAAN SAMPAH BERBASIS 3R DI DESA MORONGE KECAMATAN MORONGE KABUPATEN KEPULAUAN TALAUD - Kenedi Sugianto Larumpaa; Nixon Jefres Sindua; Jolanda Ester Kaihatu (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
The research problem is how the community responds to 3R-based waste management (Reduce, Reuse and Recycle) in the coastal area of Moronge Village, Moronge District. This study aims to determine the community's response to 3R-based waste management (Reduce, Reuse and Recycle) in the coastal area of Moronge Village, Moronge District. The research method used is a quantitative descriptive research method. The population in the coastal area is the object of research. The number of people living in the coastal areas including those still classified as close to the coast is 120 families and the sample is determined to be 25% of the population so the sample is 30 families. The results of this study indicate the results of (1) reduce is to reduce something that causes waste, thus there are about 80% of respondents who think that the condition of waste in the coastal area of Moronge Village, Moronge District is very concerned about its existence, (2) reuse is an attempt to reuse waste. which can still be used for the same or different functions, thus around 83.3% of respondents agree that if there is a part of the waste that can still be used, (3) recycle is an activity or effort to recycle or recycle, thus there are around 86.7% of respondents agreed if there was an effort or effort made to utilize waste that could still be used in the form of recycling.